ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL UNTUK MENINGKATKAN BERPIKIR KREATIF SISWA - Dianisa Wahyuni; Lutvia Ainun Hazizah; Nabilla Nur Fauziah; Ridla Adawiyyah; Deti Rostika (STKIP Subang, 2023)
ABSTRACTThis study aims to describe the use of digital learning media in an effort to improvestudents' creative thinking skills. The research method used in this research isqualitative research, which is in the form of a literature review, also called aliterature study. Literature study is one method of collecting and reading fromvarious sources of articles or other journals. Research conducted in literature isresearch that is used by searching, then collecting, reading, and analyzing someliterature, both sourced from books, journals, articles, and so on. Based on theresults of the research that has been done, it is concluded that the use of digitallearning media can improve students' creative thinking skills.